Co‐infection status of novel parvovirus's (PPV2 to 4) with porcine circovirus 2 in porcine respiratory disease complex and porcine circovirus‐associated disease from 1997 to 2012. Issue 4 (18th October 2020) - Lagan Tregaskis, Paula; Staines, Anthony; Gordon, Alan; Sheridan, Pauline; McMenamy, Michael; Duffy, Catherine; Collins, P. J.; Mooney, Mark H.; Lemon, Ken
Abstract: As global pig health diseases, porcine respiratory disease complex (PRDC) and porcine circovirus‐associated disease (PCVAD) generate substantial economic losses despite pigs been vaccinated against the primary causative virus, highlighting the importance of understanding virome interactions and specifically co‐factor infections. Established primary endemic pathogens for PRDC include porcine circovirus 2 (PCV2), porcine reproductive and respiratory syndrome virus (PRRSv) and swine influenza virus (SIV), and PCV2 aetiology in interaction with other co‐infecting viruses can result in PCVAD. Porcine parvovirus (PPV) 1 is a well‐characterized virus with an available vaccine preventing reproductive failure in sows. However, whilst novel PPV 2 to 7 viruses have been identified since 2001, their viral pathogenic potential in clinical and subclinical disease remains to be determined. Therefore, this study has sought to develop a better understanding of their potential role as associated co‐infections in PRDC and PCVAD by examining archival samples for the presence of PCV2 and the novel parvoviruses PPV2‐4 from clinically diseased pigs across production age stages. Epidemiologically, the novel PPV2 was found to be the most prevalent within the fattener age group with PPV2‐4 statistically associated with pig respiratory disease and enteric ulcers. Additionally, statistical modelling by latent class analysis (LCA) on veterinary pathology scored pigs found a clustering co‐factor association between PPV2 and PCV2, suggesting the novel PPV may be involved in PRDC and PCVAD. Phylogenetic analysis of novel PPVs revealed the PPV2 capsid evolution to be diverged from the original strains with a low nucleotide homology of 88%–96% between two distinct clades. These findings determine that novel PPV 2–4 viruses are statistically associated as co‐infectors in a diseased pig population, and significantly detected PPV2 clustering co‐infection frequency with PCV2 in PRDC and PCVAD diseased pigs through LCA analysis.